2004
DOI: 10.1016/j.ultsonch.2004.01.018
|View full text |Cite
|
Sign up to set email alerts
|

The microscopic visualisation of the sonocrystallisation of ice using a novel ultrasonic cold stage

Abstract: This work reports dynamic video images of the influence of ultrasonic cavitation on the sonocrystallisation of ice at a microscopic level. This has been achieved through the construction of a unique ultrasonic system for an optical microscope. The system consists of (1). an ultrasonic cold stage, (2). a temperature control system, and (3). a microscope and imaging setup. This allows the temperature of a sample to be systematically controlled while it is subjected to simultaneous excitation with alternating pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 11 publications
1
46
0
Order By: Relevance
“…It was shown with 15% sucrose solution [27] that microbubbles generated by cavitation acted as nucleation sites for ice formation (Fig. 8).…”
Section: Ultrasonic Crystallization and Freezing (Sonocrystallization)mentioning
confidence: 95%
See 2 more Smart Citations
“…It was shown with 15% sucrose solution [27] that microbubbles generated by cavitation acted as nucleation sites for ice formation (Fig. 8).…”
Section: Ultrasonic Crystallization and Freezing (Sonocrystallization)mentioning
confidence: 95%
“…Probably the most significant application in this respect is the use of ultrasonic cutting devices. These machines utilize the high-frequency acoustic vibrations (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) to provide a smooth and clean cut for both hard and soft cheeses, minimizing wastage [4,5,56]. Ultrasound has also been commercialized as a method of sealing milk containers and packages of grated cheese -in a process also referred to as ultrasonic welding, the temperature induced by the cavitation processes described above is sufficient to seal the plastic [38,83].…”
Section: Ultrasound In Dairy Processing Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that nucleation rate shows an order of magnitude rise with sonication, while growth rate (and hence the dominant crystal size) reduces with sonication as compared to a mechanically agitated system used for crystallisation. Observations have pointed towards bubbles as a cause for melting due to their random motion [15]. Such random motion of the cavitation bubble is also associated with breakdown of ice dendrites as they form (shown in Fig.…”
Section: Mechanism Of Sonocrystallisationmentioning
confidence: 97%
“…It is logical to anticipate that these phenomenon are amplified by application ultrasound. Cavitation occurring on, or near, crystal surfaces causes intense shear stresses which can lead to secondary nucleation [18,20,72,73]. It is suggested that ultrasound energy overcomes the kinetic barriers to nucleation by reducing the activation energy, and hence reducing the induction time.…”
Section: Sonocrystallisationmentioning
confidence: 99%